Systematical position and paleoecology of the endemic deer Megaceroides algericus Lydekker, 1890 (Cervidae, Mammalia) from the late Pleistocene-early Holocene of North Africa - (:unkn) unknown (My University, 2016)
The unusual cranial morphology of the endemic extinct African deer Megaceroides algericus (Lydekker, 1890) is described. Some details of cranial and dental morphology suggest that M. algericus is closely related to the Eurasian giant deer Megaloceros giganteus (Blumenbach, 1799). The paper presents also a discussion on paleoecology and functional morphology of M. algericus, as well as its origin, phylogenetic and taxonomic position. Megaloceros mugarensis (Di Stefano, 1996) from the middle Pleistocene of Levant is regarded as a probable forerunner of M. algericus.
Keywords: African Research